Strengthening legal protection for communities that own electronic land certificates as a result of technology development - Damanik, Ade Irawan (Privietlab, 2025)
The rapid development of technology driven by globalization has transformed many aspects of legal and administrative systems, including land administration, in Indonesia. The implementation of electronic land certificates (E-certificates) aims to improve the efficiency, transparency, and legal certainty of land services. However, this transformation also introduces various legal and technical challenges, such as data security vulnerabilities, cyber threats, insufficient infrastructure, and low levels of digital literacy among the public. These issues increase the risk of data misuse and weaken legal protection for landowners, especially lower-income communities that face difficulties accessing digital resources and defending their rights. This study emphasizes the importance of strengthening legal protection mechanisms for holders of electronic land certificates by improving cybersecurity systems, establishing clear procedural regulations for dispute resolution, and enhancing digital literacy across society. Additionally, legal policies must align with the values of Pancasila and the 1945 Constitution to ensure fairness, inclusivity, and sustainability in the protection of land ownership rights. Strengthening legal certainty and data protection is crucial for realizing a safe and equitable digital land administration system in Indonesia.